5 - Cameroon, Equatorial Guinea, and the management of Equatoguinean Refugees from 1960 to 1979 - Delmas Tsafack (Afrika Zamani, 2022)
From the colonial period to the end of the dictatorial regime of Macías Nguema in Equatorial Guinea, many Equatoguineans were forced into exile by the authorities of that state. Anti-colonial struggles and the repression by Macías Nguema caused a massive influx of refugees into Cameroon. Some of these refugees worked in Cameroonian plantations. The Spanish colonial authorities in Equatorial Guinea accused the government of Cameroon of exploiting their citizens in their various industrial plantations in Bandjock and Akonolinga. The Cameroonian government, in response, denied having used the refugees in contravention of international laws. This article analyzes the presence of Equatoguinean refugees in Cameroon as well as the controversy and tensions surrounding their use in industrial plantations in Cameroon between 1960 and 1979. It concludes that while allegations of abuse of Equatoguineans in Cameroonian industrial plantations are difficult to substantiate, there is evidence that Cameroon did provide support for anti-colonial and dissident Equatoguinean exiles, which negatively affected the relations of the governments of President Ahidjo and Macías Nguema.